THE ENGLISH PROFICIENCY OF SOCIAL SCIENCE CLASS OF GOC OF MAN 2 TULUNGAGUNG - Basuni, Muh. (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
This article is intended to discuss the English competence or the English mastery level of the social science students of Global Oriented Class (GOC) of MAN 2 Tulungagung as reflected from the score of their English proficiency test. The English proficiency test administered for this research is TOEFL preparation test developed by Pearson Longman Education incorporation. The research method employed is descriptive quantitative since the purpose of this research is to describe the current conditions of the students, in this case to describe to what extent the Social Science students of Global Oriented Class are proficient in English. The finding shows that the highest of their TOEFL Preparation Test is 440 and the lowest score is 323. The mean of their score is 361.8. The finding shows that in general the students? English proficiency level is still under the standard of 400 set up by the Ministry of Religion Affairs. Further, to be able to compete globally or internationally, the students still need to work hard since if it is compared to the standard score of the overseas university admission, their proficiency score is far below 500.